ADMINISTRATIVE PROCEDURES IN THE FIELD OF TAXATION: CONCEPT AND CONTENT (Bulletin of criminological association of Ukraine, 2024)
The scientific article analyzes the scientific positions of scientists on the understanding of administrative procedures in the field of taxation. It is noted that scientists focus on considering administrative procedures through the prism of the administrative and legal status of a public authority in the field of taxation, through the appropriate set of powers to resolve an administrative case on the merits and make a corresponding decision in the form of an administrative act, which generally corresponds to the content of the norms of current legislation. It is proven that the administrative procedure in the field of taxation has certain features (signs): 1) is regulated by administrative and procedural norms; 2) is a sequence of organizational and administrative actions that are carried out in a certain order and are coordinated with each other; 3) is purposeful in nature; 4) the goal is the implementation of not only the substantive norms of tax legislation, but also the substantive norms of other legal branches; 5) is completed by the adoption of an individual administrative act. The author provides his own understanding of the category "administrative procedure in the field of taxation".
Keywords: procedure; legal procedure; administrative procedure; administrative act; public authorities; tax authorities; taxation; collection of taxes and fees